Comparison of operational costs and production of fresh tuna products; before and during the Covid-19 pandemic in Talaud Islands Regency, North Sulawesi Province - Naung, Pelia; Luasunaung, Alfret; Andaki, Jardie A.; Suhaeni, Siti; Kaligis, Erly Y.; Manembu, Indri S. (AQUATIC SCIENCE & MANAGEMENT, 2021)
Covid-19 pandemic has implications for all aspects of fishery activities in Indonesia, one of them is negative impact on the supply chain of the fishery business. To find out more about this impact, the study was aimed to determine the condition, in general, of tuna capture fisheries in the Talaud Islands Regency before and during the Covid-19 Pandemic, and to find out the comparison of operational costs and production of fresh tuna at the level of fishermen and intermediary traders in the area in both periods. Data collection was carried out in April 2020 to March 2021. Three districts in the area were selected as research locations, namely Salibabu, Gemeh, and South Essang. Surveys using questionnaires were conducted on respondents at predetermined locations. Comparative analysis using t-test was applied in this study. The results showed that the pandemic has caused, among other things, a decline in fish prices, effect in community's economy, and a decrease of tuna production. Tuna production is particularly important because while it affected the production, the operational costs remained constant. This occurs at all levels, both at the level of fishermen and at the level of intermediary traders. It can be concluded that the Covid-19 pandemic has had an impact on fresh tuna fishing activities in the area where fresh tuna production has decreased and tuna buying traders are not operating. In particular, the operational costs of catching tuna at the fisherman's level are the same, both before and during the pandemic. Meanwhile, tuna production has decreased dramatically during the pandemic. This also happens at the level of intermediary traders.Indonesian title:Â Komparasi biaya operasional dan produksi produk tuna segar pada masa sebelum dan selama Pandemi Covid-19 di Kabupaten Kepulauan Talaud, Provinsi Sulawesi Utara